The Impact of Electronic Service Quality’s Dimensions on Customer Trust for Online Travel Agencies in India - Dutta, Sabyasachi; Chauhan, R.K.; Chauhan, Kavita (Turizam, 2017)
The ever increasing internet, mobile and credit card penetration along with government efforts to boost tourism, a rising middle class, and an increasing disposable income has ensured that online travel agencies in India are going to enjoy a high growth period. The only way to sustain their business in this highly competitive yet low-margin environment is to acquire and retain customers by improving customer trust and perceived value. The focus is to understand the impact of electronic service quality’s dimensions on customer trust while they use online travel agencies in India. It will help online travel agencies to deploy resources correctly to strengthen processes which impact trust the most. Additionally, it will help guide existing online travel agencies and future entrants to have an in-depth understanding of the dimensions of electronic service quality that are information availability, ease of use, graphic style, privacy, and security of their websites.